2020
DOI: 10.15698/mic2020.12.738
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining phagosome integrity during fungal infection: do or die?

Abstract: Professional phagocytes represent a critical node in innate immunity and tissue homeostasis through their specialized ability to eat, drink, and digest material from the extracellular milieu. The degradative and microbicidal functions of phagocytes rely on the fusion of lysosomes with endosomal compartments such as phagosomes, resulting in the digestion and recycling of internalized prey and debris. Despite these efforts, several particularly dangerous infections result from a class of tenacious pathogens that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7B). As the phagolysosomal environment restricts C. albicans hyphal growth 66 , we also measured hyphal growth over time in WT and IRE1 ΔR macrophages and found that C. albicans hyphal growth is increased at 4 hpi in IRE1 ΔR macrophages (Fig. 7C).…”
Section: Resultsmentioning
confidence: 99%
“…7B). As the phagolysosomal environment restricts C. albicans hyphal growth 66 , we also measured hyphal growth over time in WT and IRE1 ΔR macrophages and found that C. albicans hyphal growth is increased at 4 hpi in IRE1 ΔR macrophages (Fig. 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Growing hyphae generate physical forces that lead to rupture of the phagosome membrane, ultimately piercing of macrophage plasma membranes, and escape within a few hours (Dunker et al, 2021; Ghosh et al, 2009; McKenzie et al, 2010; Westman et al, 2018; Westman et al, 2020). Host cells can counteract the phagosomal membrane stress to a certain degree by folding internalized hyphae (Bain et al, 2021) or enlarging the phagosome via lysosomal fusion events (Domingues et al, 2022; Westman et al, 2020; Yang et al, 2020).…”
Section: Escape From Macrophagesmentioning
confidence: 99%